Analysis of the Influence of Product Attributes and Consumer Characteristics on Consumer Preferences and Purchase Decisions of Vitamin C Oral Products During The Covid-19 Pandemic - Kurnia Kusumawati; Sahat Saragi; Lies Putriana (Enrichment : Journal of Management, 2021)
During the Covid-19 pandemic, there was an increase in sales of vitamin C products. A preliminary survey of 57 people aged 18-60 years showed that the most oral vitamin C products consumed is 500 mg and buying decisions was influenced by several things. This study aims to analyze the effect of product attributes and consumer characteristics on consumer preferences and buying decisions for oral vitamin C products during the COVID-19 pandemic. This study was an explanatory quantitative study of 159 respondents who purchased 500 mg oral vitamin C products. Respondents was men and women, aged 18-60 years, bought 500 mg oral vitamin C products without a doctor's prescription at pharmacies in Bogor district, West Java during December 2020 - January 2021 and were not in the healing period. Data was collected by purposive sampling and analyzed by SEM (Structural Equation Modeling) using the Second Order Confirmatory Factor Analysis technique using the Lisrel program. The results showed that the product attributes of 500 mg oral vitamin C had no significant effect on consumer preferences and buying decisions. Consumer characteristics have a significant effect on consumer preferences and buying decisions for 500 mg oral vitamin C products. Consumer preferences have a significant effect on buying decisions for 500 mg oral vitamin C products. During the COVID-19 pandemic, personal psychological factors which are consumer characteristics have the most significant influence on consumer preferences in choosing and buying decisions of 500 mg oral vitamin C products, followed by socio-economic factors and cultural factors.